A core outcome set for research on the management of otitis media with effusion in otherwise-healthy children. (July 2020) - Liu, Paul Zhaobo; Ismail-Koch, Hasnaa; Stephenson, Kate; Donne, Adam J.; Fergie, Neil; Derry, Jo; Stynes, Gill; Kamani, Tawakir; Birchall, John P.; Daniel, Mat
Abstract: Introduction: A Core Outcome Set (COS) is an agreed list of outcome domains to be reported by all studies investigating a condition. A COS for Otitis Media with Effusion (OME) in children with cleft palate exists (called MOMENT), but there isn't one for otherwise-healthy children. This study investigates whether the MOMENT COS could also be applicable to otherwise-healthy children. Methods: A long list of potential outcomes was generated (independently of MOMENT) via three methods: literature review to establish which outcomes are reported by OME studies, a review of outcomes contained in OME questionnaires, and a focus group asking parents of children with OME what matters to them. The long list drawn up using these sources identified no outcomes additional to ones in the MOMENT long list. An online questionnaire was subsequently undertaken, asking parents/guardians and professionals/researchers whether they think that the MOMENT final list outcomes would also be applicable to otherwise healthy children. Results: A total of 134 people took part: 53 parents/guardians (recruited through UK NHS hospitals) and 81 professionals/researchers (recruited internationally). Overall, 128 (95.5%) agreed that the MOMENT outcomes can also apply to otherwise healthy children (100% parents/guardians, 92.6% professionals/researchers). Conclusions: The outcome domains identified in the COS for OME management in children with cleft palate can also be used in otherwise-healthy children.